Developing Decentralized Applications: A Framework Approach on Blockchain Networks - Alencar, Frank Castilio; Ferreira, Carlos Henrique; Leite Filho, Dionisio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2024)
Context: Based on blockchain technologies, decentralized applications (DApps) are on the rise. Studies reveal that these systems are being developed without adherence to specific methodological criteria. Therefore, it is imperative to establish a systematic approach to their construction, allowing developers to focus on their research problems. Problem: The lack of clear guidelines for creating DApps is a challenge, making it difficult for new researchers and developers to enter this field. Research attempting to fill this gap often fails to address specific issues. Solution: This article is based on a systematic literature review with the purpose of creating a framework to support developers in decision-making, making it easier to choose the necessary technologies for DApp development. IS Theory: This study was developed under the aegis of argumentation theory and its fundamental pillars: data, security, and conclusions. Method: The research adopts a prescriptive approach and relies on a systematic literature review to formulate the decision-making framework. Summary of Results: The systematic literature review revealed the absence of a similar framework to what was developed in this work. This framework provides guidance for selecting decentralized platforms according to DApp requirements. Contributions and Impact in the IS area: The use of the developed framework will simplify the architecture design phase of decentralized information systems, as the choice of a decentralized platform for executing smart contracts guides the use of specific technologies.